Budaya Organisasi Sekolah Belajar Sukma Bangsa: Studi Analisis Nilai Inti Organisasi Pembelajaran (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This article is a report study on the development of a learning school management model of Lhokseumawe Sukma National School and the promotion of educational standards with the aim of sustainable educational development. The research focuses on the school profile of Sukma Nation students and the achievements and challenges of the program in its implementation. The study is qualitative and uses survey methods. Information gathered through documents and interviews with relevant authorities, including focus group observations. The study also presents various manifestations of Sukma Bangsa school innovations. The results specifically show that institutional leadership is related to the implementation of five main categories of learning schools, which are personal leadership, shared vision, mental models, situated thinking and group learning. The order of applications according to the system can be seen in the changes in the behavior of the individual regarding information management, information sharing, interpretation and information search. In addition, the student and school management model has become an important part of achieving school effectiveness.